The influences of e-service quality and customer loyalty of dropee / Zulfahmi Zulkifle - Zulkifle, Zulfahmi (Bachelor of Business Administrations (Hons) Marketing, 2018)
The Internet business area or eCommerce is one of the quickest developing and most alluring ventures in Malaysia. The most recent gauge by Statista uncovered that the Online business stage has earned the revenue to US$3,144m before the finish of 2018. Besides, the industry is relied upon to produce US$5,457m in revenue by 2022. The selection of eCommerce business stages in the previous years has enormously expanded due to the surge of internet users. ("eCommerce - Malaysia I Statista Market Forecast," n.d.)